Case report: Left ventricular perforation caused by right ventricular pacemaker lead - Huang, Xiang; Zhou, Heng; Li, Xiao-Mei; Li, Xiao-Lan (Frontiers in Cardiovascular Medicine, 2023)
Background Perforation of the interventricular septum and left ventricular (LV) free wall by a right ventricular (RV) lead is an extremely rare and potentially life-threatening complication. In this case report, we discussed the diagnosis and management of a very unusual complication of pacemaker (PM) implantation, i.e., LV perforation brought on by an RV pacing lead. Case summary A 92-year-old man was admitted to Xiangyang No.1 People’s Hospital due to a complete atrioventricular block. We performed a dual-chamber PM implantation; however, on the second postoperative day (POD), pacemaker failure occurred. Thoracic computed tomography (CT) scan showed that RV lead had pierced the interventricular septum and LV free wall. A transvenous lead extraction of the penetrating lead was performed uneventfully, and RV lead was refixed at the lower RV septum on the 5th POD. Discussion Identification of high-risk patients is mandatory to prevent this serious complication, and transvenous lead extraction with cardiac surgery backup may be an option.